Role of platelet-rich fibrin in enhancing the viability of autologous microlobular fat graft: an animal-based experimental study (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Tissue fat has been used as a fat graft in plastic reconstructive surgery since ancient times by surgeons. However, an issue with this usage is that fat gets absorbed by up to 30-50%, especially centrifuged fats. The aim of this study was to compare the survival of microlobular fat, centrifuged fat, microlobular fat with plateletrich fibrin (PRF), and centrifuged fat with PRF. METHODS Subcutaneous fat was taken from the stomach area and divided into two parts, microlobular fat and centrifuged fat, and processed by adding PRF as follows: 1) microlobular fat without PRF; 2) microlobular fat with PRF; 3) centrifuged fat without PRF; and 4) centrifuged with PRF. These fat grafts were implanted into rabbit earlobes. Each procedure was performed repeatedly nine times for a total of 36 repetitions for all groups. RESULTS Microscopic evaluation revealed the highest number of adipocytes in the microlobular fat with PRF group (mean = 1,932) and the highest number of fibroblasts (mean = 600.5) compared to those in other treatment groups, although the difference was not statistically significant. There was more neovascularization in the microlobular fat group (mean = 228.5), but it was not statistically significant. CONCLUSIONS Addition of PRF to microlobular fat graft enhances the number of adipocytes and fibroblasts, including the enhancement of neovascularization.